Makna verba Gada sebagai polisemi dalam novel Saseoham Baeksiphoeui Upyeonmul karya Lee Do Woo - Defia, Citha; Herniwati, Herniwati; Samsudin, Didin (Jurnal Pendidikan Bahasa dan Sastra, 2021)
Polysemy includes linguistic forms that have multiple interrelated meanings. Polysemy was chosen as the research theme, intended to find the meaning variations of verb gada, the cause of polysemy verb gada, and the meaning relationship of polysemy verb gada. The present research departs from the difficulty of interpreting verb gada, based on the context. This research applied a qualitative approach with a descriptive research methods. Then the sentences containing the verb gada from a novel entitled â€œSaseoham Baeksiphoeui Upyeonmulâ€ written by Lee Do Woo were the data set. The data collection was carried out using documentation method with observation and note taking techniques. After the data have been collected, the analysis was carried out using content analysis method. The results showed that there are different meanings of the verb gada outside the basic meaning according to the context of the sentence, which is categorized as the extended meaning. The discovery of the extended meaning then showsÂ  polysemy of verb gada which is caused by several factors: shift of usage, figurative, specialization of meaning, and euphemism. The proof that the meanings found are polysemy of verb gada was marked by the presence of metaphor, which showed the relationship of similarity, and metonymy, which showed the relationship of contiguity.